1991
DOI: 10.1002/bjs.1800780904
|View full text |Cite
|
Sign up to set email alerts
|

Postsplenectomy sepsis and its mortality rate: Actualversusperceived risks

Abstract: A collective critical review of the literature on postsplenectomy sepsis from 1952 to 1987 has been undertaken. The reports cover a cohort of 12,514 patients undergoing splenectomy but of these only 5902 reports were sufficiently detailed to allow a useful analysis. The incidence of infection after splenectomy in children under 16 years old was 4.4 per cent with a mortality rate of 2.2 per cent. The corresponding figures for adults were 0.9 per cent and 0.8 per cent respectively. The present analysis of well d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
254
3
10

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(281 citation statements)
references
References 123 publications
4
254
3
10
Order By: Relevance
“…, before the availability of Hib conjugate vaccine, found that most cases of postsplenectomy infection are caused by S pneumoniae (57% of cases), followed by H influenzae (6%), N meningitidis (4%), and Escherichia coli (4%), with a 32-77% case fatality rate. 1 The widespread use of Hib conjugate vaccine appears to influence the prevalence of causative organisms of postsplenectomy infection. Passive surveillance data in the UK, based on 77 cases of postsplenectomy infection between 1994 and 1998, showed that S pneumoniae and N meningitidis accounted for 87% and 3% of cases, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, before the availability of Hib conjugate vaccine, found that most cases of postsplenectomy infection are caused by S pneumoniae (57% of cases), followed by H influenzae (6%), N meningitidis (4%), and Escherichia coli (4%), with a 32-77% case fatality rate. 1 The widespread use of Hib conjugate vaccine appears to influence the prevalence of causative organisms of postsplenectomy infection. Passive surveillance data in the UK, based on 77 cases of postsplenectomy infection between 1994 and 1998, showed that S pneumoniae and N meningitidis accounted for 87% and 3% of cases, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…P atients without spleens are at a significantly increased risk of serious infection with encapsulated bacteria, especially Streptococcus pneumoniae, Haemophilus influenzae type b (Hib), and Neisseria meningitidis. 1 Antibiotics and polysaccharide pneumococcal, meningococcal, influenza, and Hib conjugate vaccines are available for the prevention of postsplenectomy infection and are recommended for all splenectomised patients by the Department of Health (DoH) and the British Committee for Standards in Haematology (BCSH), with the exception of meningococcal polysaccharide vaccine. 2 3 Because the adherence to preventive measures has been reported to be low, 4 5 we conducted this study to determine the coverage of appropriate vaccination and antibiotic prophylaxis in splenectomised patients in Scotland during an 11 year period from 1988 to 1998.…”
mentioning
confidence: 99%
“…1,2 On removal of the spleen the incidence of severe infections increases both in children and adults, 3,4 and there are changes in many immunologic parameters. 5 One lasting change is a high increase in the number of B lymphocytes in the blood, an effect that is constantly observed both in humans 6 and in experimental animals, 7,8 and that comparably affects the 2 compartments of the blood, the peripheral and the marginal pools.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the expression of molecules involved in initial adhesion of lymphocytes to the endothelium, in transmigration through the endothelium and the tissue, and in B-cell activation within the tissue was analyzed in all B-cell subsets in blood, lymph nodes, and bone marrow (␣ 4 [11][12][13][14] ). The functional consequences of possible changes in surface molecule expression were tested in vitro by adhesion assays and in vivo by following the traffic of labeled B cells from blood to thoracic duct lymph.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Mortality is 50-70% in post-splenectomy sepsis, even when optimal antibiotic therapy and supportive care are provided. [7] In the early post-splenectomy period, complications including hemorrhage, adjacent organ injury, wound infection, pancreatitis, and pleural effusion may occur. Patients treated with a non-operative method are protected against all of these complications.…”
Section: Discussionmentioning
confidence: 99%